Snežni plazovi v Sloveniji Geografske značilnosti in preventiva - Pavšek, Miha (Geografija Slovenije, 2002)
In comparison to other disasters, snow avalanches endanger only a small part of surface of Slovenia, but they are problematic mostly because of their spatial and temporal unpredictability. Focusing on alpine landscape, the author studies the natural geographical characteristics of snow avalanches.